1997
DOI: 10.1161/01.str.28.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Carotid Intima-Media Thickness and Symptomatic and Asymptomatic Peripheral Arterial Disease

Abstract: Although the prevalence of advanced atherosclerosis was very low, small changes in IMT were associated with clinically significant development of atherosclerosis in the peripheral arteries. However, further longitudinal studies are needed that standardize measurement techniques and would allow accurate comparisons across studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
185
1
26

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(222 citation statements)
references
References 36 publications
10
185
1
26
Order By: Relevance
“…Kollias and colleagues reported that the left‐side IMT was higher and more closely related to CV risk factors (mainly systolic BP) than that on the right side in children 35. Several other studies also demonstrated that IMT is higher on the left side than the right side in middle‐aged or older populations 36, 37. These results were consistent with our study to some extent.…”
Section: Discussionsupporting
confidence: 93%
“…Kollias and colleagues reported that the left‐side IMT was higher and more closely related to CV risk factors (mainly systolic BP) than that on the right side in children 35. Several other studies also demonstrated that IMT is higher on the left side than the right side in middle‐aged or older populations 36, 37. These results were consistent with our study to some extent.…”
Section: Discussionsupporting
confidence: 93%
“…In several studies of IMT in several age groups all measurements were performed without taking atherosclerotic lesion into account [6,7]. In means that data were received by measurements in full range from plaque free to significant atherosclerotic lesion zones of carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…An important predictive phenotype for human cardiovascular disease is carotid IMT (23,24). Measuring the IMT may be the best method for detecting early atherosclerosis and assessing the subsequent risk of cardiovascular events (stroke, myocardial infarction and peripheral vascular disease) (24)(25)(26)(27).…”
Section: Three Biological Laws Define Vascular Remodellingmentioning
confidence: 99%